Researches on the subject of “Violence Against Women”: A bibliometric analysis since 2000 - Yıldırım, İ. Esen; Ergüt Özlem (My University, 2016)
The purpose of this study is to measure the existing scientific contribution on the subject of “violence against women (VAW)” since 2000. The data set of this research is compiled of the articles searched by the keyword “violence against women” on Web of Science (WOS) data base. These articles were analyzed bibliometrically according to their annual frequency, field of interest, country, institution, journals they were published in and their authors in five-year periods since 2000. Besides the social network among countries, institutions and authors contributed to the VAW literature was disclosed. It is observed that there had been a significant increase in the scientists’ interest on the subject of VAW since 2000. It is also remarkable that the USA stands out as the leading country on this subject in all the three periods. The academic cooperation between the authors and the universities that are studying on the subject of VAW has been improved especially starting from 2010. It is believed that the obtained data in this study and presented social network structures among countries, universities and authors would serve as a guide for the improvement of future international cooperative works among the leading universities and researchers that study to protect the women against the violence.
Keywords: Violence Against Women,Bibliometrics,Social Network Analysis,Web of Science